Biomarkers reflecting disturbed gut barrier under treatment with TNF inhibitors in radiographic axial spondyloarthritis - Denis Poddubnyy; Hildrun Haibel; Fabian Proft; Mikhail Protopopov; Valeria Rios Rodriguez; Murat Torgutalp; Judith Rademacher; Laura Spiller; Christine Maria Hempel (RMD Open)
Objectives The objective of this study is to investigate lipopolysaccharid-binding protein (LBP), zonulin and calprotectin as markers of bacterial translocation, disturbed gut barrier and intestinal inflammation in patients with radiographic axial spondyloarthritis (r-axSpA) during tumour necrosis factor inhibitor (TNFi) therapy and to analyze the association between disease activity, response to treatment and biomarker levels.Methods Patients with active r-axSpA of the German Spondyloarthritis Inception Cohort starting TNFi were compared with controls with chronic back pain. Serum levels of LBP, zonulin and calprotectin were measured at baseline and after 1 year of TNFi therapy. We analysed the longitudinal association between biomarkers and disease activity, and the relationship between biomarkers and treatment response with regression analysis.Results 121 patients with r-axSpA were compared with 63 controls. At baseline, patients with r-axSpA had higher levels of LBP and calprotectin than controls, which decreased significantly during TNFi treatment. LBP showed a positive association in longitudinal analyses with Axial Spondyloarthritis Disease Activity Score (ASDAS) (ß=0.08, 95% CI 0.06 to 0.10), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) (ß=0.08, 95% CI 0.04 to 0.12) and C reactive protein (CRP) (ß=1.69, 95% CI 1.04 to 2.34). Calprotectin was associated with ASDAS (ß=0.04, 95% CI 0.01 to 0.07) and CRP (ß=0.82, 95% CI 0.27 to 1.37). Furthermore, LBP and calprotectin levels at baseline showed an association with a subsequent change in BASDAI. Baseline zonulin levels were not significantly associated with disease activity or treatment response.Conclusion Serum levels of LBP and calprotectin are associated with disease activity in patients with r-axSpA and decrease with TNFi response. In contrast, serum zonulin levels showed no association with disease activity or treatment response, arguing against a strict correlation between intestinal permeability and disease activity in axSpA.